2014
DOI: 10.3727/096368914x678391
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Maintained Stem Cell Pluripotency and Increased Proliferation Rate by Activating Jak2–Stat3 Combined with EGFR–Erk1/2 Pathways

Abstract: Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) are considered the most powerful in terms of differentiating into three-germ-layer cells. However, maintaining self-renewing ESCs and iPSCs in vitro requires leukemia-induced factor (LIF), an expensive reagent. Here we describe a less expensive compound that may serve as a LIF substitute-salvianolic acid B (Sal B), a Salvia miltiorrhiza extract. We found that Sal B is capable of upregulating Oct4 and Sox2, two genes considered important for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To date, there were several strategies to enhance the reprogramming efficiency, including knockdown of p53 gene 9 , hypoxic conditions 10,11 , epigenetic modification 12 , regulation of microRNAs 13 and addition of small molecular compounds 14,15 . In 2003, one group reported a near 100% reprogramming efficiency in mouse and human cells via OKSM transduction and Mbd3 depletion 16 .…”
mentioning
confidence: 99%
“…To date, there were several strategies to enhance the reprogramming efficiency, including knockdown of p53 gene 9 , hypoxic conditions 10,11 , epigenetic modification 12 , regulation of microRNAs 13 and addition of small molecular compounds 14,15 . In 2003, one group reported a near 100% reprogramming efficiency in mouse and human cells via OKSM transduction and Mbd3 depletion 16 .…”
mentioning
confidence: 99%
“…The present study indicated that salvianolic acids were the most water-soluble in Salvia miltiorrhiza Bunge (14). Salvianolic acid B (Fig.…”
Section: Introductionmentioning
confidence: 51%
“…The current study demonstrated that salvianolic acid B significantly upregulated p-STAT3 protein expression in CSVD rat. Liu et al (14) reported that salvianolic acid B increased proliferation rate by activating Janus kinase 2-STAT3 pathways in stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…This expense has limited the number of labs that can participate in stem cell research and has encouraged efforts to find a viable alternative. Several studies have shown that dimethyl sulfoxide (DMSO) ( Yi et al, 2020 ), salvianolic acid B ( Liu et al, 2014 ), and cordycepin ( Wang et al, 2020 ) could maintain the expression of pluripotency markers in mESCs cultured in the absence of LIF; however, the developmental pluripotency of these mESCs was elusive.…”
Section: Discussionmentioning
confidence: 99%